2010
DOI: 10.1148/radiol.09091437
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid Aortic Valve: Four-dimensional MR Evaluation of Ascending Aortic Systolic Flow Patterns

Abstract: Four-dimensional flow MR imaging showed abnormal helical systolic flow in the ascending aorta of patients with a BAV, including those without aneurysm or aortic stenosis. Identification and characterization of eccentric flow jets in these patients may help identify those at risk for development of ascending aortic aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
304
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 382 publications
(342 citation statements)
references
References 33 publications
34
304
0
4
Order By: Relevance
“…Barker et al and Hope et al were the first to link eccentric flow patterns in BAV disease with WSS, as measured with 2D flow MRI and 4D flow MRI, respectively 29, 30. Similar to our study, maximum systolic WSS was found in different aortic regions for RL‐BAV and RN‐BAV.…”
Section: Discussionsupporting
confidence: 88%
“…Barker et al and Hope et al were the first to link eccentric flow patterns in BAV disease with WSS, as measured with 2D flow MRI and 4D flow MRI, respectively 29, 30. Similar to our study, maximum systolic WSS was found in different aortic regions for RL‐BAV and RN‐BAV.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, increased vortex flow provides the potential haemodynamic basis for the development of aortopathy. 18,39,40 Our findings suggest that BAV relatives are more likely to have altered aortic shapes associated with abnormal aortic blood flow patterns, which have been associated with pathologic aneurysmal dilatation. Additional studies in larger cohorts are warranted to investigate the impact of aortic shape on flow patterns in the absence of valvular disease.…”
Section: Discussionmentioning
confidence: 69%
“…Bicuspid aortic valves produce distinctive helical blood flow patterns within the aorta, a finding that supports the importance of hemodynamics in the progressive aortopathy seen with BAV (16,17). While valve replacement improves transvalvular gradients and relieves patient symptoms, studies using advanced three-dimensional MRI blood flow imaging ("4D Flow") have shown that ascending aortic flow patterns remain markedly abnormal despite aortic valve replacement (18).…”
mentioning
confidence: 77%